PENERAPAN STRATEGI PEMASARAN DALAM PENINGKATAN VOLUME PENJUALAN PADA TOKO ARIFIN SPORT MEDAN - Ramos, Elton Ramos (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
In running a small and medium business, usually using a relatively small amount of capital, and the business actors have less experience in marketing their products to consumers. This has an impact on the achievement of the level of income that will be achieved, and can also result in bankruptcy due to many problems faced, such as few sales, too little capital, and many competitors. The purpose of this study is to find out how the marketing strategy is carried out by the Arifin Sport Store in determining the products, prices, promotions, and places applied to increase sales. The type of research used in this study is qualitative, namely research that is descriptive and tends to use narratives. The data collection technique for this study uses observation, interviews and documentation. The results of this study indicate that the marketing strategy carried out by the Arifin Sport store is to have quality products, prices according to product quality, less strategic distribution locations and lack of media used in promoting product sales.